Full‐profile search–match by the Rietveld method. Issue 3 (14th May 2019) - Lutterotti, Luca; Pillière, Henry; Fontugne, Christophe; Boullay, Philippe; Chateigner, Daniel
Abstract : A new fully automatic search–match procedure based on a Rietveld full‐pattern‐fitting method is presented. The method does not rely on peak positions and permits not only phase identification but also a quantification of the phases and their gross microstructural features. Abstract : A new search–match procedure has been developed and tested which, in contrast to previously existing methods, does not use a set of lines identified from a diffraction pattern, but an optimized Rietveld fitting on the raw data. Modern computers with multicore processors allow the routine to be fast enough to perform the entire search in a reasonable time using quite large databases of crystal structures. The search–match is done using the crystal structures for all phases and the instrumental geometry, and as such can be applied to every kind of diffraction experiment, including X‐rays, thermal/time‐of‐flight neutrons and electrons. The methodology can also be applied to nanocrystalline samples for which peak identification may be a problem. A web interface has been developed to permit easy testing and evaluation of the procedure. The quality of the results mainly depends on the availability of the sought phase in the structure database. The method permits not only phase identification but also a rapid quantification of the phases and their gross microstructural features, provided the instrumental function is known.